Pathogenesis of Functional Biliary Pain and Pharmacology of Trimebutin - E. L. Bueverova; O. Yu. Zolnikova; N. L. Dzhakhaya; A. V. Sedova; V. Т. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to provide data on the pathogenesis of functional biliary pain and provide rationale for the use of trimebutine for this indication.Key points. Biliary pain is one of the most frequent reasons for patients to see a doctor. The diagnosis of functional disorder of the gallbladder and Oddi's sphincter is legitimate only after the exclusion of organic causes from both the gastrointestinal tract and other organs and systems. The initial appeal to surgeons with a complaint of pain in the epigastrium or right hypochondrium may lead to unjustified surgical intervention that does not bring relief to the patient's suffering. The consequences of cholecystectomy also have an anatomical and physiological justification for the occurrence or preservation of biliary pain. Currently, two main hypotheses are being considered to explain its cause: increased intraluminal pressure due to morphological and functional obstacles to bile outflow and visceral hypersensitivity. In the multilevel system of regulation of the gallbladder and sphincter apparatus, the opioid system occupies a special place. The agonist of peripheral receptors of the enkephalinergic system, trimebutine, in clinical studies led to the relief of biliary pain in more than 80 % of patients with functional biliary disorders, while a significant decrease in the severity of diarrhea, dyspeptic, and constipation syndromes was revealed.Conclusion. The prescription of the peripheral receptor agonist of the enkephalinergic system, trimebutine, is pathogenetically justified for functional biliary pain.